Centred discourse, decentred practice: the relational production of Russian and Chinese 'rising' power in Central Asia. Issue 8 (3rd August 2019) - Heathershaw, John; Owen, Catherine; Cooley, Alexander
Abstract: This paper challenges dominant understandings of 'rising powers' by developing a decentred, relational account of Russia and China in Central Asia. We ask whether Moscow and Beijing's regional integrative strategies do not guide, but rather are led by, everyday interactions among Russian and Chinese actors, and local actors in Central Asia. Rising powers, as a derivative of 'Great Powers', are frequently portrayed as structurally comparable units that concentrate power in their executives, fetishise territorial sovereignty, recruit client states, contest regional hegemony and explicitly oppose the post-1945 international order. In contrast, we demonstrate that the centred discourse of Eurasian integration promoted by Russian and Chinese leaders is decentred by networks of business and political elites, especially with regard to capital accumulation. Adopting Homi K. Bhabha's notion of mimicry (subversion, hybridity) and J. C. Scott's conception of mētis (local knowledge, agency), and using examples of Russian and Chinese investments and infrastructure projects in Central Asia, we argue that in order to understand centring discourse we must look to decentring practices at the periphery; that is, rising power is produced through ongoing interactions between actors at the margins of the state's hegemonic reach.